Evaluation of quality assurance for school health services in primary health care centers at Al-Numaniyah District. Iraq - Ghassan A Washi; Naji Y Saadoon (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: School Health Services (SHS) is commonly considered to be one of the more crucial parts of the health program in schools, and they are responsible for the students' overall health. Active school health services aid in the early detection and prevention of illnesses among students. SHS are those that are worried with the health and educational attainment of students at an appropriate age by providing direct services of health care to students in coordination with the administration and staff of the school. AIMS: To evaluate the quality assurance for school health services in all essential components as structure, process, and outcome and identify the correlation between them. MATERIALS AND METHODS: A descriptive study consists of (171) respondent selected by convenient sample distributed on (6) main primary health care centers, (32) health and nursing staff, and (133) consumers (school principals) at Al-Numaniya district from July 5, 2022 to January 25, 2023. Questionnaire comprised of three forms distributed on structure, process, and outcome data, which were collected by interview and researcher observation with directors of main primary health care centers, health and nursing staff, and school principals and through the use of a descriptive statistical (frequencies, percentages, statistical mean) and inferential (Pearson correlation coefficient) and the data were analyzed. RESULTS: Showed overall evaluation of the quality assurance related to structure standards of primary health care centers PHCs was fair (66.7%). Regarding process standards showed that 50.0% of the nurses' staff expressed a fair activity and duties. On the other hand, regarding outcome showed that 64.7% of the school principals expressed somehow satisfied toward elementary school health care services. CONCLUSIONS: Overall evaluation of quality assurance regarding school health services in PHCs was fair as described by moderate average in all essential components as structure, process, and outcome. It also showed a significant positive correlation between outcomes of quality assurance for school health services and regard structure of PHCs. RECOMMENDATIONS: Ministry of Education and Health can benefit from the study to identify the strengths and weaknesses in the structure of PHCs. Equipping health centers with essential supplies such as computers, vaccines, eye glasses, and laboratory materials PHCs to provide integrated services for students.